Quercetin inhibited epithelial mesenchymal transition in diabetic rats, high-glucose-cultured lens, and SRA01/04 cells through transforming growth factor-β2/phosphoinositide 3-kinase/Akt pathway. (5th September 2017) - Du, Lei; Hao, Meng; Li, Chengcheng; Wu, Wenya; Wang, Wenwen; Ma, Zhongxuan; Yang, Tingting; Zhang, Nan; Isaac, Adelusi Temitope; Zhu, Xia; Sun, Ying; Lu, Qian; et al.
Abstract: Diabetic cataract (DC), an identified life-threatening secondary complication of diabetes mellitus, has proven to be a dilemma because of its multifactorial caused and progression. An increasing number of studies have shown that in addition to the maillard reaction, enhanced polyol pathway, and oxidative insults, epithelial mesenchymal transition (EMT) is related to the prevalence of DC. Quercetin, a classic flavonoid with multiple pharmacological effects has been reported to possess therapeutic efficacy in the management and treatment of this disease. However, the mechanism underlying its therapeutic efficacy in EMT of lens epithelial cells (SRA01/04) and contribution to resolving DC remains a mystery. Therefore, in this study, we investigated the effects of quercetin on EMT of SRA01/04 and high-glucose (HG)-induced lens opacity accompanied by lens fibrosis induced by type-1 diabetes. Furthermore, we sought to clarify the specific mechanisms underlying these effects. At week 14 after streptozotocin (STZ) intraperitoneal administration, diabetic rats showed lens opacity accompanied with diminished antioxidant function, enhanced polyol pathway activity, and non-enzymatic glycation. Western blotting confirmed EMT in rat SRA01/04 cells with significantly increased α-smooth muscle actin (α-SMA) and decreased E-cadherin expressions. Treatment of the lens with quercetin ameliorated the oxidative stress, inhibited aldose reductase (AR) activation, reduced advanced glycation end product (AGE) production, and finally suppressed EMT in the early stages. Our in vitro results showed that high-glucose activated the transforming growth factor-β2/phosphoinositide 3-kinase/protein kinase B (TGF-β2/PI3K/Akt) signalling and EMT in SRA01/04 cells. Further, induced oxidative stress, activation of aldose reductase, and accumulation of advanced glycation end products were also involved in this process. Quercetin was potent enough to effectively ameliorate the high glucose (HG)-induced EMT of SRA01/04 cells by inhibiting the activation of TGF-β2/PI3K/Akt, enhancing the antioxidant capacity, inhibiting AR activity, and reducing AGE production. From the whole animal to tissues, and finally the cellular level, our results provide considerable evidence of the therapeutic potential of quercetin for DC. This might be due to its inhibition of EMT mediated through inhibition of the TGF-β/PI3K/Akt pathway. Highlights: We guess quercetin could present efficient measure towards the management/treatment of DC. Effect of quercetin on EMT of lens epithelial cells (SRA01/04), HG-induced lens opacity and lens fibrosis from type-1 diabetes was investigated. After which we clarify the specific mechanisms underlying these effects. Our results confirmed that quercetin was formidable enough to effectively ameliorate high glucose-induced EMT. TGF-β2/PI3K/Akt pathway inhibition, antioxidant status enhancement and AGEs reduction prove to be responsible for quercetin's effect.